2021
DOI: 10.1002/wer.1651
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of direct waste‐activated sludge dewatering benefits and costs in a water resource recovery facility

Abstract: Dewatering of anaerobic digested (AD) sludge containing waste‐activated sludge (WAS) from enhanced biological phosphorus removal (EBPR) poses numerous challenges including poor dewaterability, struvite scale formation, and recycling of high N and P levels in the sludge liquor to the treatment process. A full‐scale water reclamation facility was investigated to mitigate these problems by experimenting with direct dewatering of EBPR WAS, bypassing the AD step. The investigations experimented with various blends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…During dewatering, some of the soluble compounds and fine particulate matter will leave along with the water being removed. This is supported by data reported on the liquid fraction of digestate, revealing ranges of 240–5630 mg solids L −1 (Mailler et al, 2021; Mentzer et al, 2021; Sun et al, 2021). Mailler et al (2021) reported high phosphorus (P: 71 mg L −1 ) and ammonium concentrations (NH 4 + : 389 mg L −1 ) in the liquid fraction.…”
Section: Resultssupporting
confidence: 81%
“…During dewatering, some of the soluble compounds and fine particulate matter will leave along with the water being removed. This is supported by data reported on the liquid fraction of digestate, revealing ranges of 240–5630 mg solids L −1 (Mailler et al, 2021; Mentzer et al, 2021; Sun et al, 2021). Mailler et al (2021) reported high phosphorus (P: 71 mg L −1 ) and ammonium concentrations (NH 4 + : 389 mg L −1 ) in the liquid fraction.…”
Section: Resultssupporting
confidence: 81%
“…Phosphorus removal processes have a direct impact on sludge dewatering properties. In terms of EBPR process, the impacts on sludge dewatering are clear and wellestablished [79,80]. Generally, sludge from the EBPR process is more difficult to dewater [80].…”
Section: Impact Of Phosphorus Management Scheme On Sludge Treatmentmentioning
confidence: 99%
“…In terms of EBPR process, the impacts on sludge dewatering are clear and wellestablished [79,80]. Generally, sludge from the EBPR process is more difficult to dewater [80]. Phosphorus release during sludge treatment is accompanied by the release of cations, of which the divalent ions are then deposited quickly.…”
Section: Impact Of Phosphorus Management Scheme On Sludge Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A case study which investigated an alternative sludge treatment processing strategy which led to whole plant chemical use reduction and operating cost reduction was described by Mentzer et al (2021). The major goal of this study was to enhance the dewaterability of final sludge being sent to a landfill for disposal.…”
Section: Operational Strategies At the Whole Facility Levelmentioning
confidence: 99%